The dream that kicks : the prehistory and early years of cinema in Britain - Chanan, Michael (Routledge, 2003)
The Dream the Kicks is a classic account of the prehistory and early years of cinema in Britain. In this new paperback edition, which has been thoroughly revised to take into account recent scholarship of early cinema, Michael Chanan provides a fasciniating account of the rich and hitherto hidden history of the origins of film. Chanan demonstrates that the theory of `the persistence of vision', which led to the invention of moving pictures, has been superceded by modern scientific findings. In its place, he puts forward a theory of invention as a type of bricolage, and sh.